Hotel and Lodging Management / An Introduction: Second Edition - Stutts Alan T; Wortman James F (John Wiley And Sons, Inc, 2006)
This book prepares readers to succeed as managers in the hotel and lodging industry, while developing a solid foundation for a long and successful career. Preface, Introduction, Growth and Development of the Lodging Industry, Organizational Structure, The Front Office, Housekeeping, The Marketing and Sales Department, Human Resource Management, Hotel Food and Beverage, Loss Prevention and Security, The General Manager, Yield Management, Management Contracts and Franchise Agreements, Time-Share and Vacation Ownership, Resorts and Themed Lodging and Special Lodging Environments, Glossary, Index.